Randomized controlled trial of oral captopril, of oral isosorbide mononitrate and of intravenous magnesium sulphate started early in acute myocardial infarction: safety and haemodynamic effects. ISIS-4 (Fourth International Study of Infarct Survival) Pilot Study Investigators. - Flather, M; Pipilis, A; Collins, R; Budaj, A; Hargreaves, A; Kolettis, T; Jacob, A; Millane, T; Fitzgerald, L; Cedro, K (1994)
The purpose of this randomized controlled study was to assess the haemodynamic effects, safety and tolerability in acute myocardial infarction (AMI) of one month of oral captopril, one month of oral isosorbide mononitrate and 24 h of intravenous magnesium. It was carried out in four United Kingdom and six Polish hospitals in consecutive phases: oral captopril vs oral mononitrate vs placebo were compared among 400 patients in a 'three-way' study; and then oral captopril vs placebo and oral mononitrate vs placebo were compared among 474 patients in '2 x 2' and '2 x 2 x 2' factorial studies (with 208 patients in the latter study also randomized between intravenous magnesium and open control). The factorial studies differed from the three-way study in that one group of patients was allocated both oral captopril and oral mononitrate, a higher maintenance dose of captopril was used (following the same initial dose), and once daily controlled-release mononitrate was used. In the three-way study, the mean of the lowest systolic blood pressures recorded during the first 4 h after randomization were (mmHg +/- standard error): 104 +/- 2 captopril vs 105 +/- 1 mononitrate vs 112 +/- 2 placebo (P < 0.001 for captopril or for mononitrate vs placebo), and in the factorial studies were 105 +/- 1 captopril vs 110 +/- 1 placebo (P < 0.01) and 106 +/- 1 mononitrate vs 108 +/- 1 placebo (NS). There was an excess of hypotension recorded among patients allocated active treatment (captopril > mononitrate > placebo) and there was a small, but significant, excess of cardiogenic shock with captopril compared with control in the factorial study. However, in these studies, neither captopril nor mononitrate were associated with any overall increase in the incidence of hypotension considered severe enough to lead to treatment being stopped. No other serious complications were observed, and compliance with study tablets at hospital discharge was not significantly different between the active and placebo groups. Patients allocated magnesium in the 2 x 2 x 2 factorial study had a slightly lower mean systolic blood pressure just after the initial 15 min bolus injection (126 +/- 2 magnesium vs 134 +/- 3 control; P < 0.05) but there were no significant differences during the subsequent 24 h maintenance infusion period. Apart from some facial flushing, magnesium did not appear to be associated with any complications.(ABSTRACT TRUNCATED AT 400 WORDS)